The Use of Financial Quiz Websites on Controlling Impulsive Shopping Behavior - Aripradono, Heru Wijayanto; Natalia , Sherly Celia (Newinera Publisher, 2024)
This study aims to develop a financial quiz website designed to help control impulsive buying behavior, particularly among women aged 18-24 in Batam City. The Design Thinking approach was applied in the development process, following five stages: Empathize, Define, Ideate, Prototype, and Testing. The results show that the